Traumatic chest injury in children: A single thoracic surgeon's experience in two Nigerian tertiary hospitals - Kelechi Emmanuel Okonta (Wolters Kluwer Medknow Publications, 2015)
Background: This study was to determine the extent and outcome of childhood chest injury in Nigeria, and to compare results with that of other literatures. Patients and Methods: A Prospective study of all children under 18 years of age with chest trauma in two tertiary hospitals in Southern Nigeria from January 2012 to December 2014 was reviewed. The aetiology, type, associated injury, mechanism, treatment and outcome were evaluated. The patients were followed up in the clinic. The data were analysed using SPSS version 20.0 with a significant P < 0.05. Results: Thirty-one patients (12.1%) under 18 years of age of 256 chest trauma patients were managed in the thoracic units. The mean age was 9.78 ± 6.77 years and 27 (87.1%) were male. The aetiology in 13 was from falls, 10 from automobile crashes, 3 from gunshots, 4 from stabbing and 1 from abuse. The highest peak of chest injury was on Saturday of the week and April of the year. The pleural collections are as follows: 15 (71.4%) was haemothorax, 4 (19.1%) pneumothorax, 2 (9.5%) haemopneumothorax and 18 patients had lung contusion in combination or alone with the pleural collections. Seven patients who presented >12-h versus 2 who presented <12-h and 6 of children between 0 and 9 years versus 3 at 10-18 years of age had empyema thoracis (P value not significant). One death was recorded. Conclusion: Chest trauma in children is still not common, and blunt chest injury from falls and automobile accidents are more common than penetrating chest injury. Treatment with tube thoracostomy is the major management modality with empyema thoracis as the most common complication.